2021
DOI: 10.1371/journal.pone.0246068
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological upregulation of GLT-1 alleviates the cognitive impairments in the animal model of temporal lobe epilepsy

Abstract: It is known that hippocampal epileptogenesis is accompanied by hyperexcitability, glutamate-related neuronal dysfunctions and consequently cognitive deficits. However, the neuroprotective role of astrocytic glutamate uptake through the Glutamate Transporter-1 (GLT-1) remains to be unknown in these processes. Therefore, to assess the effect of glutamate uptake, pharmacological upregulation of GLT-1 using ceftriaxone administration (200 mg/kg/day, i.p, 5 days) was utilized in Li-PIL animal models of temporal lob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…It should also be noted that CTX treatment can restore hippocampus-dependent behavioral disorders in various models of disease. For example, learning and memory ability in the Morris water maze was rescued by CTX administration during the phase of epileptogenesis in the lithium-pilocarpine model of temporal lobe epilepsy [48]. Administration of CTX for 7 days and 14 days during hypoxic exposure ameliorated hypobaric hypoxia-induced cognitive impairment in the Morris water maze and GLT1 expression [49].…”
Section: Figurementioning
confidence: 98%
“…It should also be noted that CTX treatment can restore hippocampus-dependent behavioral disorders in various models of disease. For example, learning and memory ability in the Morris water maze was rescued by CTX administration during the phase of epileptogenesis in the lithium-pilocarpine model of temporal lobe epilepsy [48]. Administration of CTX for 7 days and 14 days during hypoxic exposure ameliorated hypobaric hypoxia-induced cognitive impairment in the Morris water maze and GLT1 expression [49].…”
Section: Figurementioning
confidence: 98%
“…Recombinant forms of interleukin 1 receptor antagonists, LDN/OSU-0212320, ceftriaxone, and Parawixin10 all act by enhancing EAAT2 expression ( 18 20 ). Among them, ceftriaxone has been applied to one clinical patient, but no significant efficacy was found ( 16 , 24 , 25 ). Therefore, more clinical studies are needed to validate the efficacy of ceftriaxone in SLC1A2 -associated epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…However, tamoxifen and growth factor α-selective agonists enhance EAAT1 and EAAT2 expression through the activation of the NF-κB pathway ( 21 , 22 ). In addition, ceftriaxone, a β-lactam antibiotic, is one of the well-studied SLC1A2 modulators, and it is an EAAT2 protein enhancer that reduces neuronal death and seizure frequency ( 23 , 24 ). An animal study also showed that low doses of ceftriaxone with valproate increased GABAergic activity and decreased glutamatergic activity, favoring seizure suppression and improved cognitive function ( 25 ).…”
Section: Pathogenesis Clinical Manifestations and Treatment Of Solute...mentioning
confidence: 99%
“…56 The hippocampus has long been thought to be crucial for learning and memory in rodents, and since it is highly susceptible to injury, these functions can be easily impaired in patients with epilepsy. 57,58 Hence, neuronal damage and disorder in this area will cause cognitive deficits. Besides, numerous findings demonstrate that epilepsy, neurodegeneration and inflammatory cytokines are not autonomous, but mutually influence each other.…”
Section: Discussionmentioning
confidence: 99%